Cardiobacterium hominis Endocarditis: A Case Report and Review of the Literature - Andrew Walkty (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present case report describes the clinical course of a patient who presented with Cardiobacterium hominis endocarditis. A review of the literature follows the case presentation. C hominis, a fastidious Gram-negative bacillus, is a member of the HACEK group of microorganisms (Haemophilus species, Actinobacillus actinomycetemcomitans, C hominis, Eikenella corrodens and Kingella kingae). Endocarditis caused by C hominis is uncommon and generally follows a subacute course. Patients may present with constitutional symptoms, symptoms related to valvular destruction or symptoms secondary to embolic events. Diagnosis requires identification of the pathogen from blood or vegetation by either culture or molecular techniques. Blood cultures may require prolonged incubation, highlighting the importance of incubating blood cultures for at least two to three weeks in patients with suspected endocarditis. In the past, C hominis was generally sensitive to penicillin. However, reports of beta-lactamase-producing C hominis have appeared in the literature over the past decade. The current recommendation for first-line treatment is a third-generation cephalosporin (ceftriaxone) for four weeks (six weeks if a prosthetic valve is in place).